2022
DOI: 10.3390/foods11182863
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits and Side Effects of Short-Chain Fatty Acids

Abstract: The gut microbiota and their metabolites could play an important role in health and diseases of human beings. Short-chain fatty acids (SCFAs) are mainly produced by gut microbiome fermentation of dietary fiber and could also be produced by bacteria of the skin and vagina. Acetate, propionate, and butyrate are three major SCFAs, and their bioactivities have been widely studied. The SCFAs have many health benefits, such as anti-inflammatory, immunoregulatory, anti-obesity, anti-diabetes, anticancer, cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 121 publications
0
73
0
Order By: Relevance
“…Although BBR exhibited potential anti-BC activity in preclinical studies, there are several predicaments to overcome before it was been advanced into clinical treatment against BC. Firstly, several studies showed that BBR exhibited low toxicity to healthy cells and human beings (126,127). It could also lead to some adverse events, such as constipation and nausea (128,129).…”
Section: Discussionmentioning
confidence: 99%
“…Although BBR exhibited potential anti-BC activity in preclinical studies, there are several predicaments to overcome before it was been advanced into clinical treatment against BC. Firstly, several studies showed that BBR exhibited low toxicity to healthy cells and human beings (126,127). It could also lead to some adverse events, such as constipation and nausea (128,129).…”
Section: Discussionmentioning
confidence: 99%
“…High-fiber diets are beneficial and reduce the risk of obesity, diabetes, hypertension, and cardiovascular disease (CVD), which are common comorbidities of RA [ 15 , 16 , 56 ]. In patients with RA, approx.…”
Section: Discussionmentioning
confidence: 99%
“…Reported fiber intakes were not higher in other studies for people with RA or in the general German population [ 38 , 59 , 60 ]. Dietary fiber supplementation has a potential to close this fiber gap [ 56 ]. Interestingly, none of the patients used a dietary fiber supplement or asked for information on high-fiber food sources.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the net effects of the actions of SCFAs are context-dependent and can be pro- or anti-inflammatory ( Schilf et al, 2021 ). The exact effects of SCFAs may depend on the type of SCFAs, the delivery method, the levels and the health condition of hosts ( Xiong et al, 2022 ). Moreover, fermentation initiators such as sucrose can selectively promote SCFA production by the probiotic S. epidermidis , and improve acne dysbiosis ( Wang et al, 2016 ).…”
Section: Scfa-based Therapy For Inflammatory Skin Diseasesmentioning
confidence: 99%